The economic valuation of Gedo Natural Forest conservation benefits, Ethiopia - Tadesse Tolera (Journal of Innovation and Entrepreneurship, 2022)
Forest ecosystem economic valuation is responsible for ecologically aware and reasonable gains to the country and particularly to the surrounding groups through different means. Thus, the central objective of this study was to analyze the economic valuation Gedo Natural Forest conservation benefits of using the contingent valuation method. Both primary and secondary data were employed in this study. The interview responses of 342 households nominated from three kebeles around Gedo natural forest were collected in purpose and random sampling procedures through a semi-structure questionnaire. The mean willingness to pay calculated by means of Krinsky-Robb technique after running of Seemingly Unrelated Bivariate Probit Regression from the dichotomous choice format and open-ended questions was 24.97 and 23.91 birr per year, respectively. The outcomes of Tobit model show that the total livestock unit, total annual income of the household, and the amount of credit utilization are meaningful variables positively and significantly related to the likelihood of willingness to pay for the conservation benefits of Gedo natural forest. On the other hand, the households' family size, the households' age, and initial bid value were other important variables negatively and significantly influence households' willingness to pay for the conservation benefits of Gedo natural forest. The liable body could, therefore, apply the scenario of willingness to pay in the study area, so that the Gedo natural forest could be conserved, measurable benefit to the households could be practical, and future awareness of respective household could be raised.
Keywords: 650; Economic valuation; Gedo Natural Forest; Seemingly unrelated bivariate probit regression; Tobit model; Willingness to pay